The Impact of PQ4R Strategy Use on EFL Students' English Reading Comprehension - Nurul - Lailatul Khusniyah (EDULANGUE, 2018)
The aim of this study is to examine the effect of PQ4R strategy on reading learning at English Study Program Universitas Islam Negeri Mataram. The research was used action research method. The sampling was taken by 34 students. The validity of data used credibility, transferability, dependability, and conformability. Reading comprehension ability achievement questions prepared by the researcher. It was used as the data collecting tool. These questions were implemented to both groups before the experiment. Independent sample t-test was used for data analysis. The result of the study that t-test result is t-stat (5.38) > t-table (1.99). It means that there is a significant difference was found in reading comprehension learning